Историк на грани эпох: Павел Луппов - первый историк удмуртского народа / В. А. Бердинских ; [редактор Т. А. Пояркова] - Бердинских Виктор Аркадьевич (Удмуртия, 1991)
Экземпляры: ф.15 (1992) / Инвентарный номер: 35031 / Цена: / Сис.шифр: 63.3(2Рос.Удм) / Авт.знак: Б 48 / ГРНТИ: 03.23.55 / ББК: 63.3(2Рос.Удм)